Medellín: Innovation Capital - Higuita Palacio, Andrés Mauricio (Ingeniería Solidaria, 2015)
This article is a topical review that aims to show how Medellín (Colombia) has been advancing in projects and processes associated with innovation to the point of becoming a national and Latin American point of reference. The topic of innovation has been widely studied and enriched based on contributions by neoclassicists, with Shumpeter and the evolutionists Nelson, Winter, Lundvall and Freeman, among others. The term innovation is approached conceptually, from the conventional perspective of innovation derived from the classics and near classics, as well as the evolutionist approach to innovation and its relationship to the systemic approach, from which to derive the concepts of national and regional innovation systems. Finally, a general characterization is made of the actions that have enabled Medellín to become a regional innovation system led by the state sector, which has distinguished itself in the worldwide context to the point of the city being characterized as an innovation capital in the Latin American context.
Keywords: innovation; national innovation system; regional innovation system